Two-dimensional unconfined seepage flow toward a highway cut slope - Zerihun, Yebegaeshet T. (Acta hydrotechnica, 2023)
The unconfined gravity-flow system near a free-outflow boundary such as a highway cut slope was investigated by using a higher-order numerical model. Unlike the Dupuit–Forchheimer equation, which is applicable mainly to a hydraulic flow problem, the proposed model accounts for the effects of the vertical component of the flow for a full treatment of the problem of plane phreatic flow. The model equations were numerically solved by means of a finite-difference scheme. Their accuracy was then verified using the solutions of the full two-dimensional potential-flow method and rigorous mathematical approaches, revealing that for a face slope flatter than 70o, the differences between the solutions of the model and the earlier approaches for the relative seepage-face height were nearly negligible. The comparison results also demonstrated the substantial effects of the slope of the downstream face on this height and the seepage discharge. Furthermore, the accuracies of the model predictions for the phreatic-surface profile and the distributions of the piezometric head at different vertical sections are much better than the earlier method, which approximates the trapezoidal-shaped aquifer by its equivalent rectangular one. Such a satisfactory performance may be attributed to the model’s higher-order correction factor for the effects of the phreaticsurface curvature and steep slope.
Keywords: artificial cut; gladina podzemne vode; nehidrostatsko precejanje; non-hydrostatic groundwater flow; odtok; phreatic surface; precejanje pri prosti gladini; seepage discharge; seepage-face height; unconfined seepage flow; višina vode na precejnem robu; vkop